Application of an acclimated microbial consortium as biocatalyst for rapid determination of biochemical oxygen demand - Shahir, Shafinaz; Chun, Siang Ling; Ahamad, Rahmalan (ANSI Network, 2011)
Biochemical Oxygen Demand (BOD) is an important parameter for water pollution monitoring. Since the conventional BOD assay by American Public Health Association (APHA) takes 5 days to complete (termed BOD5), development of an alternative method that can rapidly measure the amount of biodegradable organics in wastewater is highly desirable. In the present study, single and mixed microbial cultures isolated from different environments in Malaysia were tested as potential biocatalyst in an assay called Ferricyanide Mediated-Biochemical Oxygen Demand (FM-BOD) used for rapid BOD detection. Unlike the BOD5 assay, the FM-BOD is based on biochemical degradation of organic compounds via reduction of ferricyanide as an alternative terminal electron acceptor to dissolved oxygen. The increase in concentration of microbially produced ferrocyanide during incubation of the microorganisms in the presence of ferricyanide and organic substrates was measured voltammetrically using a 10 µm platinum working electrode. Measurements were conducted using linear sweep voltammetry at potential 0-600 mV versus Ag/AgCl reference electrode. Limiting currents were determined by voltammetry at Eapp = +450 mV (vs Ag/AgCl). The amount of ferrocyanide produced was found to be proportional to the amount of biodegradable organics. From the study, it is shown that mixed microbial consortium acted as a better biocatalyst for rapid BOD detection compared to both single cultures and a commercial consortium. The microbial consortium consists of four species of microorganisms. FM-BOD assays were conducted in optimized conditions with microbial consortium at final absorbance of OD600 2.5 and ferricyanide at concentration 60 mM. Results showed that the FM-BOD assay was able to detect biodegradable organics in 1 h compared to the current BOD5 assay of 5 days. This FM-BOD assay with optimized conditions is applicable to food wastewater consisting of easily degradable carbon source.